Get Up, Please : Poems - Kirby, David, 1944- (Book collections on Project MUSE., 2016)
In comical and complex poems, David Kirby examines our extraordinarily human condition through the lens of our ordinary daily lives. These keenly observant poems range from the streets of India, Russia, Turkey, and Port Arthur, Texas, to the imaginations of fellow poets Keats and Rilke, and to ruminations on the mundane side of life via the imperfect sandwich. Whether remembering girls' singing groups of the 1950s or recounting a child asking his priest if his dog would go to heaven, Kirby has the ability to make us laugh, but he can also bring us to tears through our laughter.